ANALISA KINERJA APARATUR DALAM PENANGNAN ANAK TERLANTAR DI KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Razak, Reza Abdul; Setiawan, Irfan (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2023)
The increase in the number of neglected children with social welfare problems is due to the fact thatthe services provided for people with social welfare problems are still not optimal. Several factorsoften influence this, such as the service and budget aspects provided by the government. This researchwas carried out with the aim of finding out how abandoned children are handled in Berau Regency.This research uses qualitative methods, Primary Data comes from Social Service officials such as datafrom observations and interviews, then secondary data comes from on-site documentation and otheronline sources. The results of the research show that the performance of the apparatus in handlingabandoned children at the Berau Regency Social Service through the Program for People with SocialWelfare Problems can be classified as good in terms of objectives, standards, feedback, motives andopportunities for feedback, motives and opportunities. However, it is still lacking in terms of human resource objectives that include data and competency of the apparatus at the Berau Regency SocialService.